Variasi Konsentrasi Alfa Siklodekstrin dan Waktu Sentrifugasi Dalam Preparasi Serum Lipemik Pada Pemeriksaan Glukosa Metode GOD-PAP - Izzati, Arfa; Riyani, Ani (Jurnal Teknologi Laboratorium, 2018)
Examination of glucose levels of the GOD-PAP method in serum may be disrupted by the presence of turbidity caused by lipemic serum, thus causing high false serum glucose levels to result. The addition of alpha-cyclodextrin (α-CD) may bind the lipemic in serum. This study aims to find out how the concentration and time of optimal centrifugation with the addition of alpha-cyclodextrin. Added variation alpha-cyclodextrin concentration 0.5%, 1%, and 1.5% in pooled serum with variation concentration of triglycerides ± 1000 mg/dL, ± 1500 mg/dL and ± 2000 mg/dL incubated for 30 minute at 4°C. Centrifuged at 3000 rpm with variation of centrifugation time for 5 minutes, 10 minutes and 15 minutes at 4°C to form precipitate and supernatant. Then the supernatant measured the glucose GOD-PAP and triglycerides GPO-PAP using a photometer. The result were no significant differences in variations centrifugation time and variations alpha-cyclodextrin concentrations after comparison with serum glucose pooled levels (base line) in the ANOVA test, Kruskall Wallis Test and Mann Whitney test. There was no significant difference with pooled serum (base line) at the time of triglyceride concentration ± 1000 mg/dL with alpha-cyclodextrin concentration 0.5% and centrifugation time at 10 minute, triglyceride concentration ± 1500 mg/dL and ± 2000 mg/dL with alpha-cyclodextrin concentration 1%, centrifugation time at 5 minute.